Evaluación ambiental de la influencia de las condiciones climáticas en 3 densidades de siembra del (cucumis sativus L.) “Pepinillo” fundo Miraflores – San Martín - Torres Flores, Raquel (2012)
At present there is much variability of the climate as a result of the accelerated process of deforestation, consumption of fossil :fuels, etc., and their effects are very noticeable in many places on Earth. In our region San Martín, the climatic variability has been very visible in the different epochs of planting of crops, prolonged periods of drought, rising and falling of the rainfall regime~, etc.,, resulting in irregularities in the performance. This research work is oriented in the Environmental Assessment of the influence of climatic conditions in three densities of planting the crop of gherkin, made in the Miraflores Fundo, belong to the San M.artin National University- Tarapoto. There are presents the general background of en:vironmental assessments of the weather conditions made for different crops as well as theoretical definitions of sorne authors with respect to the subject matter. The project consisted of a field researcb to detemñne the behavior of the cultivation ofpickle compared to climatic variations at different times ofthe year. Employment is a randomized complete block design with a factorial arrangement 2x3 (DBCA with 02 times and 03 densities). We also use the Omlcan test with a reliability of 95 %, with the purpose to estimate if there are significant differences between blocks and the two different eras of planting, as weU as the interaction between them. The evaluation was performed through the plant monitoring of the incidence of pests and diseases, as well as an evaluation of tbe impact tbrougb a descriptive analysis in a simple chart of the abiotic environment (water, soil) and the biotic environment (flora and fauna), Considering to the socioeconomic way with bis components of economy, health and safety as points of evaluation of tbe impacts of the climatic variations. In addition tbere was done the comparison of the meteorological information of the project by the meteorological information of 1 O years ago behind (historical boss) by the aim to see die va.riatious of maximum average temperature, minimal average temperature and total rainfall. Key words: Climate variability, pickle.